2017
DOI: 10.18203/2320-1770.ijrcog20175004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of post-partum intrauterine contraceptive device in vaginal and intra caesarean insertion

Abstract: INTRODUCTIONInstitutional deliveries have increased all over the country, thereby providing opportunities for quality postpartum family planning services. In this period, women are highly receptive and motivated to accept family planning methods. Ideally birth to birth interval is 36 months; but 61% of births in our country are shorter then recommended interval. 27% of births occur within 24 months, 34% births between 24 to 35 months after a previous birth. In the first postpartum year, 65% of women have an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…In this study we found that there is no case of uterine perforation present in our study which is similar to study conducted by various authors [8][9][10] . This may be due to good selection and better management of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…In this study we found that there is no case of uterine perforation present in our study which is similar to study conducted by various authors [8][9][10] . This may be due to good selection and better management of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, Around 85% (170) women had inadequate awareness of the method and had declined to use as PPIUCD due to no previous knowledge or information The acceptance rate was 12% was similar with some other related studies. In other study it was found that the acceptance rate was not increasing over a long period of time [12][13] . The age group that showed the higher acceptance rate was between 25-30 years (35%).…”
Section: Discussionmentioning
confidence: 78%
“…The mean age of acceptors in vaginal group was 26.28±4.367 years and in LSCS group it was 26.02±3.67 years. Kanwat et al reported that mean age of acceptors was comparable in the both groups, being 24.42±3.79 years in vaginal and 24.20±3.42 years in cesarean group [8].…”
Section: Discussionmentioning
confidence: 93%